2019
DOI: 10.4049/jimmunol.202.supp.198.11
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus disease severity is associated with distinct CD8+ T cell profiles

Abstract: Most infants are infected with RSV by their second birthday. Despite known risk factors such as prematurity or congenital heart disease, most hospitalized infants are previously healthy. The mechanisms underlying the immunopathology of severe disease is incompletely understood. Our objective was to compare T cell profiles in nasal aspirates between infants with moderate and severe RSV disease hospitalized without immune deficiencies or congenital heart disease, during 2014–2017. Infants requiring intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies have revealed that tumour progression can result from imbalances between tumour progression and the host immune response 25 . In present study, tumour‐infiltrating immune cells results manifested high‐RAD51AP1 samples were infiltrated in Th2 cells, which was considered as the pro‐tumour cell implicated in severe disease 26 . Tumour infiltrating lymphocytes (TILs), including T cells, B cells and NK cells, that exhibited anti‐tumoural functions, 27,28 especially CD8 + and CD4 + T cells were infiltrated in low‐level RAD51AP1 group.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies have revealed that tumour progression can result from imbalances between tumour progression and the host immune response 25 . In present study, tumour‐infiltrating immune cells results manifested high‐RAD51AP1 samples were infiltrated in Th2 cells, which was considered as the pro‐tumour cell implicated in severe disease 26 . Tumour infiltrating lymphocytes (TILs), including T cells, B cells and NK cells, that exhibited anti‐tumoural functions, 27,28 especially CD8 + and CD4 + T cells were infiltrated in low‐level RAD51AP1 group.…”
Section: Discussionmentioning
confidence: 61%